Reinterpretasi Imunitas DPR dalam Sistem Ketatanegaraan Indonesia: Harmonisasi Prinsip Equality Before the Law - Kambu, Fany; Rakia, Alwiyah Sakti Ramdhon Syah; Yati, Sri (Universitas Semarang, 2025)
This study aims to analyze the implementation of the House of Representatives' right to immunity in the Indonesian constitutional system and its conformity with the principle of equality before the law. The right to immunity is granted to protect the freedom of members of the House of Representatives in carrying out their legislative duties without irrelevant legal intervention. However, its application often causes controversy, especially when it is misused to avoid legal responsibility. The background of this study stems from the tension between the right of immunity and the principle of equality before the law, which gives rise to negative public perceptions of the integrity of the DPR. This study uses a normative juridical approach with a descriptive-analytical method of analysis of primary, secondary, and tertiary legal materials. The results showed that although the right of immunity is necessary to maintain legislative independence, there is potential for abuse that undermines the principle of justice and erodes public trust in the DPR. Therefore, strict supervision by the Council of Honorary Court (MKD) and regulatory revisions are needed to ensure that this right is not abused to avoid legal liability. This study makes a significant contribution to existing literature by revealing the tension between the immunity rights of members of the House of Representatives and the principle of equality before the law, as well as highlighting the impact of the abuse of immunity rights on public trust in the legislature. In contrast to previous research, which generally focused on the right to immunity in general, this research emphasizes the potential abuse of this right and its impact on the image of the legislature. The implications of this research emphasize the need for a balance between the protection of the rights of members of the House of Representatives and legal certainty for all citizens, in order to support a more just and transparent democratic system. Penelitian ini bertujuan untuk menganalisis implementasi hak imunitas DPR dalam sistem ketatanegaraan Indonesia dan kesesuaiannya dengan prinsip equality before the law. Hak imunitas diberikan untuk melindungi kebebasan anggota DPR dalam menjalankan tugas legislatif tanpa intervensi hukum yang tidak relevan. Namun, penerapannya sering menimbulkan kontroversi, terutama ketika disalahgunakan untuk menghindari tanggung jawab hukum. Latar belakang penelitian ini berangkat dari ketegangan antara hak imunitas dan prinsip kesetaraan di hadapan hukum, yang memunculkan persepsi negatif masyarakat terhadap integritas DPR. Penelitian ini menggunakan pendekatan yuridis normatif dengan metode analisis deskriptif-analitis terhadap bahan hukum primer, sekunder, dan tersier. Hasil penelitian menunjukkan bahwa meskipun hak imunitas diperlukan untuk menjaga independensi legislatif, terdapat potensi penyalahgunaan yang merugikan prinsip keadilan dan menurunkan kepercayaan publik terhadap DPR. Diperlukan pengawasan ketat oleh Mahkamah Kehormatan Dewan (MKD) serta revisi regulasi untuk memastikan hak ini tidak disalahgunakan untuk menghindari pertanggungjawaban hukum. Penelitian ini memberikan kontribusi signifikan terhadap literatur yang ada dengan mengungkapkan ketegangan antara hak imunitas anggota DPR dan prinsip kesetaraan di hadapan hukum, serta menyoroti dampak penyalahgunaan hak imunitas terhadap kepercayaan publik terhadap lembaga legislatif. Berbeda dengan penelitian sebelumnya yang umumnya fokus pada hak imunitas secara umum, penelitian ini lebih menekankan pada potensi penyalahgunaan hak imunitas tersebut dan dampaknya terhadap citra legislatif. Implikasi penelitian ini menegaskan perlunya keseimbangan antara perlindungan hak anggota DPR dan kepastian hukum bagi seluruh warga negara, guna mendukung sistem demokrasi yang lebih adil dan transparan.